Phantom Limb Sensation (PLS) and Phantom Limb Pain (PLP) among Young Landmine Amputees - POOR ZAMANY NEJAT KERMANY, Mahtab; MODIRIAN, Ehsan; SOROUSH, Mohammadreza; MASOUMI, Mahdi; HOSSEINI, Maryam (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Poor Zamany Nejat Kermany M, Modirian E, Soroush M, Masoumi M, Hosseini M. Phantom Limb Sensation (PLS) and Phantom Limb Pain (PLP) Among Young Landmine Amputees. Iran J Child Neurol. Summer 2016; 10(3):42-47. Abstract Objective To determine the frequency of phantom limb sensation (PLS) and phantom limb pain (PLP) in children and young adults suffering landmine-related amputation. Materials & Methods All youths with amputation due to landmine explosions participated in this study. The proportions of patients with phantom limb sensation/pain, intensity and frequency of pain were reported. Chi square test was used to examine the relationship between variables. Comparison of PLP and PLS between upper and lower amputation was done by unpaired t-test. Results There were 38 male and 3 female with the mean age of 15.8±2.4yr. The mean interval between injury and follow-up was 90.7±39.6 months. Twelve (44.4%) upper limb amputees and 11 (26.8%) lower limb amputees had PLS. Nine (33.3%) upper limb amputees and 7 (17.1%) lower limb amputees experienced PLP. Of 27 upper limb amputees, 6 (14.6%) and among 15 lower limb amputees, 6 (14.6%) had both PLS and PLP. One case suffered amputation of upper and lower limbs and was experiencing PLS and PLP in both parts. PLS had a significant difference between the upper and lower amputated groups. Significant relationship was observed between age of casualty and duration of injury with PLP. Conclusion Phantom limb sensation and pain in young survivors of landmine explosions appear to be common, even years after amputation. References Nikolajsen L, Jensen TS. Phantom limb pain. Br J Anaesth 2001; 87:107-16. Tseng CC, Chen PY, Lee YC. Successful treatment of phantom limb pain and phantom limb sensation in the traumatic amputee using scalp acupuncture. Acupunct Med 2014;32(4):356-8. Davis RW. Phantom sensation, phantom pain, and stump pain. Arch Phys Med Rehabil 1993;74:79–91. Jensen TS, Krebs B, Nielsen J, Rasmussen P. Phantom limb, phantom pain and stump pain in amputees during the first 6 months following limb amputation. Pain 1983;17(3):243–256. Gupta R. FRCA, FFPMRCA, EDRA. Pain Management. Phantom Pain Syndromes. 2014, pp 71-74. Davidson JH, Khor KE, Jones LE. A cross-sectionalstudy of post-amputation pain in upper and lower limb amputees,experience of a tertiary referral amputee clinic. Disabil Rehabil 2010;32(22):1855-62. Hirsh AT, Dillworth TM, Ehde DM, Jensen MP. Sex differences in pain and psychological functioning inpersons with limb loss. J Pain. 2010; 11(1): 79–86. Anwar F. Phantom limb: Review of literature. KMUJ. 2013; 5(4): 207-12. Ephraim PL, Wegener ST, MacKenzie EJ, Dillingham TR, Pezzin LE. Phantom pain, residual limb pain, and back pain in amputees: results of a national survey. Arch Phys Med Rehabil 2005; 86(10):1910-19. Husum H, Resell K, Vorren G,Heng YV, Murad M, Gilbert M, et al. Chronic pain in land mine accident survivors in Cambodia and Kurdistan. SocSci Med 2002; 55(10):1813-6. Wartan SW, Hamann W, Wedley JR, McColl I. Phantom pain and sensation among British veteran amputees. Br J Anaesth 1997; 78(6):652-9. Krane EJ, Heller LB. The prevalence of phantom sensation and pain in pediatric amputees. J Pain Symptom Manage 1995; 10(1): 21-9. Wilkins KL, McGrath PJ, Finley GA, Katz J. Phantom limb sensations and phantom limb pain in child and adolescent amputees. Pain 1998; 78(1): 7–12. Mariane L. Simmel. Phantom experiences following amputation in childhood. J Neurol Neurosurg Psychiat 1962; 25(1): 69-78. Mohammadi Seilabipour N, Mohammadi Fallah S, Kazemi H, Shariat SV. Phantom limb correlates among amputee war veterans. Adv Cognitive Sci 2013; 15(2): 32-9. Modirian E, Shojaei H, Soroush MR, Masoumi M. Phantom pain in bilateral upper limb amputation. DisabilRehabil 2009; 31(22): 1878-81. Explosive remnants of war-Unicef. http://www.unicef. org/sowc2013/focus_war_remnants.html Rayegani SM, Aryanmehr A, Soroosh MR, Baghbani M. Phantom Pain, Phantom Sensation, and Spine Pain in Bilateral Lower Limb Amputees: Results of a National Survey of Iraq-Iran War Victims’ Health Status. JPO 2010; 22(3): 162-165. Subedi B, GrossbergGT. PhantomLimbPain:Mechanisms and Treatment Approaches. Pain Res Treat 2011, Article ID 864605, 8 pages. Laura L. Burgoyne, Catherine A. Billups, José L. JirónJr, Roland N. Kaddoum, Becky B. Wright, George B. Bikhazi, et al. Phantom limb pain in young cancer-related amputees: Recent experience at St. Jude Children’s Research Hospital. Clin J Pain 2012; 28(3): 222–5. Sin EI, Thong SY, Poon KH. Incidence of phantom limb phenomena after lower limb amputations in a Singapore tertiary hospital. Singapore Med J. 2013; 54(2): 75-81. Melzack R, Israel R, Lacroix R and Schultz G. Phantom limbs in people with congenital limb deficiency or amputation in early childhood. Brain 1997; 120(9): 1603– 20. Rahimi A, Mousavi B, Soroush M, Masumi M, Montazeri A. Pain and Health-Related Quality of Life in War Veterans with Bilateral Lower Limb Amputations. Trauma Mon2012; 17(2):282-286. Ketz AK. The experience of phantom limb pain in patients with combat-related traumatic amputations. Arch Phys Med Rehabil 2008, 89(6): 1127-32. Boyle M, Tebbi CK, Mindell ER, Mettlin CJ. Adolescent adjustment to amputation. Med Pediatr Oncol 1982; 10(3): 301-12. Patricia A. McGrath, Loretta M. Hillier. Phantom limb sensations in adolescents: A case study to illustrate the utility of sensation and pain logs in pediatric clinical practice. J Pain Symptom Manage 1992; 7(1): 46–53. Vida L. Tyc. Psychosocial adaptation of children and adolescents with limb deficiencies: A review. Clin Psychol Rev 1992; 12(3); 275–291.